New evidence of connections between increased O‐GlcNAcylation and inflammasome in the oral mucosa of patients with oral lichen planus - Thi Do, T.; Phoomak, C.; Champattanachai, V.; Silsirivanit, A.; Chaiyarit, P. (Clinical and experimental immunology, 2018)
Summary Oral lichen planus (OLP) is considered a chronic inflammatory immune‐mediated disease of the oral mucosa. Immunopathogenesis of OLP is thought to be associated with cell‐mediated immune dysregulation. O‐GlcNAcylation is a form of reversible glycosylation. It has been demonstrated that O‐GlcNAcylation promoted nuclear factor kappa B (NF‐κB) signalling. Activation of NF‐кB can induce expression of nucleotide‐binding domain‐like receptor family pyrin domain containing 3 (NLRP3) inflammasome, which is a large intracellular multi‐protein complex involving an immune response. Dysregulated expression of the NLRP3 inflammasome was reported to be associated with autoinflammatory diseases. No integrative studies between O‐GlcNAcylation and NLRP3 inflammasome in OLP patients have been reported. The present study aimed to determine the immunohistochemical expression of O‐GlcNAcylation, NF‐κB signalling molecules and NLRP3 inflammasome in oral mucosae of OLP patients. Oral tissue samples were collected from 30 OLP patients and 30 healthy individuals. Immunohistochemical staining and analyses of immunostaining scores were performed to evaluate expression of O‐GlcNAcylation, NF‐κB signalling molecules and NLRP3 inflammasome. According to observations in this study, significantly higher levels of O‐GlcNAcylation, NF‐κB signalling molecules and NLRP3 inflammasome were demonstrated in OLP patients compared with control subjects (P < 0·001). Positive correlations among O‐GlcNAcylation, NF‐κB signalling molecules and NLRP3 inflammasome were also observed in OLP samples (P < 0·01). In conclusion, the present study provides supportive evidence that increased O‐GlcNAcylation is associated with increased expression of NLRP3 inflammasome via the NF‐κB signalling pathway. These findings provide a new perspective on immunopathogenesis of OLP in relation to autoinflammation. Increased expression of O‐GlcNAcylation and NLRP3 inflammasome in inflamed oral mucosal tissue of oral lichen planus (OLP) patients provides new perspective on immunopathogenesis of OLP in relation to autoinflammation.